The public sector's perspective on procuring public works projects – comparing the views of practitioners in Hong Kong and Australia - Cheung, Esther; Chan, Albert P. C.; Kajewski, Stephen (Journal of Civil Engineering and Management, 2010)
Hong Kong has been one of the early jurisdictions to adopt Public Private Partnership (PPP) model for delivering large public infrastructure projects. The development of this procurement approach in Hong Kong has followed an intricate path. As such, it is believed that there are a number of areas which are interesting to unveil. As part of a comprehensive research study looking at implementing PPPs, interviews with experienced local industrial practitioners from the public sector were conducted to realize their perspective on the topic of procuring public works projects. Amongst these interviews, fourteen were launched government officials and advisers. The interview findings show that the majority of the Hong Kong and Australian interviewees had previously conducted some kind of research in the field of PPP. Both groups of interviewees agreed that “PPPs gain private sector's added efficiency/expertise/management skills” when compared to projects procured traditionally. Also, both groups of interviewees felt that projects best suited to use PPP are those that have an “Economic business case”. The interviewees believed that “Contractor's performance” could be used as key performance indicators for PPP projects. A large number of critical success factors were identified by the interviewees for PPP projects; two of these were similar for both groups of interviewees. These included “Project objectives well defined” and “Partnership spirit/commitment/trust”. Finally it was found that in‐house guidance materials were more common in the organizations of the Australian interviewees compared to the Hong Kong ones. This paper studies the views of the public sector towards the topic of PPPs in Hong Kong and Australia, which helps to answer some of the queries that both academics and the private sector in these jurisdictions are keen to know. As a result the private sector can be more prepared when negotiating with the public sector and realise their needs better, academics on the other hand are provided a wider perspective of this topic benefiting the research industry at large.First Published Online: 15 Oct 2010